Merekayasa universiti : biografi naib canselor Universiti Sains Malaysia - Sohaimi Abdul Aziz. ([Glugor], Pulau Pinang, Malaysia : Penerbit Universiti Sains Malaysia : Pengedar, Koperasi Kedai Buku Universiti Sains Malaysia, Universiti Sains Malaysia : MPH Distributors, 2012)
Collective biography of five vice chancellors of Universiti Sains Malaysia.
Includes bibliographical references (p. 147-152).
In Malay.
Keywords: Universiti Sains Malaysia -- Administration; Universiti Sains Malaysia -- History; College administrators -- Malaysia -- Biography